Comparison of serum reproductive hormones, antioxidants, PGE2 and PGF2-α between primary and secondary infertile women in Calabar - Idongesit K Isong; Chinyere AO Usoro; Zibril A Okhormhe; Dorathy C Okpokam; Christopher EJ Udiong (Asian Pacific Journal of Reproduction, 2017)
Objective: To compare the prolactin, progesterone, luteinizing hormone, follicle stimulating hormone, estradiol, antisperm antibodies, tumor necrosis factor α, total antioxidant capacity, prostaglandin E2 and F2α between primary and secondary infertile women in Calabar.Methods: One hundred and two volunteers infertile women (test group), aged 20-45 years attending the infertility clinic in the University of Calabar Teaching Hospital (UCTH) were recruited. Fourteen of the women had primary infertility while 88 of them had secondary infertility. Sixty apparently healthy, age matched women served as the control group. Five millilitres of blood was collected, allowed to clot and serum was obtained from the subjects and Enzyme Linked Immunosorbent Assay method was used for prolactin, progesterone, estradiol, follicle stimulating hormone (FSH) and luteinizing hormone (LH), prostaglandin E2 and F2α, human TNF-α, Chlamydia trachomatis IgG, antisperm antibodies assay, while serum total antioxidant capacity was assessed spectrophotometrically.Results: The result shows on comparison that primary infertile women has a significantly higher level of progesterone than those with secondary infertility (P>0.05). There was a significant difference in the levels of prolactin and total antioxidant capacity in the primary and secondary infertility when compare to the control group at P>0.05. Their mean ages were (31.10±5.37) years and (33.10±4.91) years respectively. There was a positive correlation between TAC and FSH, TNF and anti-sperm anti-bodies in the test group of r=0.207 and r=0.632; P>0.05 respectively.Conclusions: These findings suggest no alterations in levels of prostaglandin F2α, TNF and anti-oxidant between primary and secondary infertile females.